PTU-108 A UK single centre experience of management of hepatitis C virus genotype 4 infection with pegylated-interferon and ribavirin. (22nd June 2015) - Selvapatt, N; Habibi, M; Brown, A
Abstract : Introduction: New direct acting antiviral agents are revolutionising hepatitis C virus (HCV) treatment. However, to date published phase 3 clinical trial data in genotype 4 (GT4) HCV patients is limited. GT4 HCV is more common in Africa, the Middle East and Asia. In the UK, the mainstay of treatment has been pegylated interferon and ribavirin but limited data exists on outcomes in patients treated in Europe. We report the first "real-life' sustained virological response (SVR) outcomes using pegylated interferon and ribavirin for HCV GT4 in the UK, and the largest European single centre cohort. Method: HCV GT4 patients treated at a London, UK centre between 2002 and 2014 were assessed for SVR outcomes. Patient age, sex, region of origin, co-infection with HIV, pre-treatment liver biopsy histological assessment, genotype subtyping, treatment duration and dose reductions were compared against SVR outcomes on univariate analysis. Multivariate analysis was performed on results with P < 0.1. Results: During the study period 219 patients were diagnosed with HCV GT4. Of these 118 (54%) were treated with pegylated interferon and ribavirin and 57 achieved SVR (48%). The median age at the start of treatment was 48 years (range 6 to 66 years) and 72% were male. Six patients were intolerant, 25 were non responders, 3 developed breakthrough, 18 were relapsers, 3 are currently undergoing treatment and 6 lost to follow-up. Five out of 6 patients with acute HCV and HIV co-infection achieved SVR. Three HCV monoinfected patients were treated while on renal dialysis, with 2 achieving SVR. On univariate analysis age ≥ 45 (P < 0.0001), high viral load (P < 0.0001), Ishak staging 5–6 (P < 0.0001) and non-Egyptian Africans (P = 0.0059) were all negatively associated with SVR. Eastern Europeans appeared to have higher rates of SVR (P < 0.0001). Using multivariate correlation viral load (P = 0.0005); Ishak staging (P = 0.0031) and age (P = 0.0003) were associated with SVR but not country of origin (P = 0.0645). Conclusion: Outcomes with pegylated interferon and ribavirin for HCV GT4 in this "real-life" setting were sub-optimal especially in the context of newer regimens. Patients with older age, high viral loads and advanced disease need prioritisation for alternative treatments. Disclosure of interest: N. Selvapatt Conflict with: Gilead, BMS, M. Habibi: None Declared, A. Brown Speaker Bureau of: Abbvie, BMS, Gilead, Janssen, Merck.